Zaufanie jako siła wspierająca działania na konkurencyjnym rynku - Olszewska, Monika (Annales. Etyka w Życiu Gospodarczym, 2011)
The subject of the article is the trust as a specific soft value which could be considered as an important aspect of the management process. The article is an attempt of the theoretical analysis of notions such as ”trust” and provides characteristics of some management aspects, especially the personnel policy in which trust is a basic value for building an employee’s engagement and interpersonal relations. The article ends with conclusions in which the author tries to find the answer to following question: is it possible to build the enterprise’s financial advantage basing on the trust.